Spatial Equity in Devolved Healthcare: Geospatially Exploring Local Disparities in Maternal Healthcare Uptake After Devolution in Kenya - Samuel Nyangueso; Patrick Hayombe; Fredrick Owino (European Scientific Journal, ESJ, 2018)
Devolved healthcare in Kenya was to ensure provision of proximate and easily accessible services throughout the Country, thereby improving local uptake as an outcome from patient perspective. Over five years after operationalization of the devolved healthcare, it isn’t certain whether or not there have been reducing spatial disparities and/or improving prospects of spatial equity in local utilizations of essential primary healthcare. The paper seeks to explore spatial disparities in maternal healthcare utilization and prospects of realising spatial equity after devolution of healthcare in Kenya. County of Siaya and 30 Wards therein were, respectively, selected as spatially heterogeneous and homogenous multiple cases for the study through retrospective patient-based surveys. The study leveraged on Kenyan webbased health information systems to capture spatial and attribute data on skilled birth attendance and antenatal care before and after devolution by each of the 220 registered health facility the County by Wards. Local utilization ratio, a new innovative indicator, was applied to effectively measure and analyse the spatial disparities in maternal healthcare through ordinary least square spatial regression analysis within spatio-temporal analysis realm using ArcGIS 10.3. Result showed significant positive spatial relationship in maternal service utilizations before and after devolution by Wards (p<0.01, R 2>90%). but stagnating or deteriorating spatial disparities irrespective of either increasing or decreasing uptake of the services. This trend points to lower prospects by devolved healthcare in realizing spatial health equity without improving quality and comprehensiveness of primary health services in Siaya County and related decentralised units in Kenya and beyond.